TUNTUTAN PAMPASAN BAGI KES KEMALANGAN JALAN RAYA DI MALAYSIA: KAEDAH ALTERNATIF BERASASKAN DIYAT: Claim of Damages for Road Traffic Accident Cases: The Alternative of Diyat - Samudin, Siti Aisyah; Ismail, Siti Zubaidah (Journal of Shariah Law Research, 2018)
The risk of any possible damages in road accident cases may include injuries, death and property damages. Islamic law provides diyat as a compensation mechanism that could only covers bodily injuries and death caused by that accident. On the other hand, any risk of damages involving properties, the compensation in the form of daman will be imposed. It contradicts to the compensation system for injuries and deaths in Malaysia. The Civil Law Act 1956 (CLA 1956) provides compensation for general damages. In this case, the elements of indemnity, which are difficult to quantify and not conclusive appears, such as damages for future earnings loss. Therefore, the objective of this paper is to examine the compensation rate as provided in the diyat by comparing it with the CLA 1956 and the economic status today. Using the collected data analysed from the semi-structured interview and bibliography studies, the research findings indicate that compensation based on diyat according to the gold valuation is the best method and could possibly maximize the justice for road accident victims as the value is more stable compared to the other medium.